Menghujat dan Unjuk Rasa Dalam Perspektif Hukum Islam - Kurniawan, Muhammad Zuhud; Amin, Abd. Rauf Muhammad; Shuhufi, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The term demonstration/demonstration in Islamic politics has many meanings, namely muzaharah, demonstrations which are synonymous with violence (anarchy) and can also be said to be supportive actions as a form of support for individuals or groups. Another term is masirah, which is the opposite of muzaharah without ending in anarchism. Diversity, differences in views, misunderstandings, and anything that can trigger conflict among the people can be minimized. Politics is the right of every citizen. Rasulullah saw. pun is a complete figure; Apostles, heads of households, scholars, statesmen and even politicians. However, in terms of politics, the Prophet SAW. always prioritizes ethical aspects in politics. The current era of openness and freedom of opinion has become an open space for some people to voice ideas and thoughts which often turn into acts of blasphemy, criticizing, insulting, indulging in disgrace, or insulting other people or parties outside their group.